Association between chrononutrition profile and diet quality among IIUM Kuantan students - Azahari, Nuraniza; Rahim, Nurfarah Najwa (IIUM Press, 2023)
Introduction: Chrononutrition is explained as a relationship between our body's circadian rhythm, that is 24 hours cycle changes that occur in the body in terms of physical, mental and behavioral changes. Certain physiological effects play an important part in regulating 24-hour cycle body clocks, affecting a person’s eating behavior. The patterns of chrononutrition that were assessed in this study is important aspects that indicate the diet quality of IIUM Kuantan students since students are vulnerable to practice unhealthy lifestyles and poor dietary choices. Therefore, this study is aimed to determine whether there are association between chrononutrition profile and diet quality among IIUM Kuantan students. Methods: A cross-sectional study was conducted in order to determining the association between chrononutrition profiles and diet quality. A total of 129 undergraduate students participated in this study. Two questionnaires, which are Malaysia-translated version Chrononutrition Profile questionnaire (CPQ-M) and Malaysia Healthy Eating Index (M-HEI) were distributed to the targeted participants and the data was collected to be analyzed for the results of the study. Results: The data obtained were statistically analyzed by using Statistical Package for Social Sciences (SPSS 26.0). The result showed no statistical significant for association between chrononutrition profile and diet quality (p>0.05). This contradicts with our prediction, where poor or good chrononutrition profile may influence the diet quality of the students. Conclusion: Thus, there was no association between chrononutrition profiles and diet quality among IIUM Kuantan students who live in the campus.